Absorption refrigeration cycles based on ionic liquids: Refrigerant/absorbent selection by thermodynamic and process analysis. (1st March 2018) - Moreno, Daniel; Ferro, Víctor R.; de Riva, Juan; Santiago, Rubén; Moya, Cristian; Larriba, Marcos; Palomar, José
Highlights: Absorption refrigeration based on ionic liquids is analyzed by process simulation. COSMO-based/Aspen Hysys methodology is applied to perform process calculations. COSMO-RS allows selecting best thermodynamic pairs among 8 refrigerants and 900 ILs. Selection of correct refrigerant/absorbent pair is revealed a key of cycle efficiency. Optimum operating ranges are proposed for different refrigerant/IL pairs. Abstract: A COSMO-based/Aspen HYSYS methodology has been used to perform an extensive thermodynamic evaluation of potential application of ionic liquids (ILs) to absorption refrigeration cycles. By applying this a priori methodology, 7200 systems, formed by 900 ILs and 8 refrigerants, representative of available commercial/cation and refrigerant, were evaluated, which would be otherwise unviable due to the lack of experimental data. Firstly, COSMO-RS analysis was carried out for the preliminary selection of suitable ILs as absorbents for each refrigerant, by means of predicted values of Henry's Law constants of refrigerants in ILs. Selected ILs were then introduced in Aspen HYSYS simulator database by using the molecular information by COSMO-RS method. The reliability of COSMO-based/Aspen HYSYS calculations was successfully validated by comparison to available experimental data (>2700 points) of pure and mixture properties of absorbent-refrigerant systems. Then, the performance of selected ILs (and other proposed in the bibliography) in absorption refrigeration cycles was evaluated by process simulations (>230 refrigerant/IL pairs studied at 60 different operating conditions) using COSMO-based/Aspen HYSYS methodology. Cycle efficiency was analyzed in terms of the coefficient of performance (COP), solution circulation ratio ( f ratio) and the total mass flow pumped from the absorber to the generator, a new parameter proposed to compare the results obtained with different refrigerants. COSMO-based/Aspen HYSYS methodology allowed the selection of adequate refrigerant-absorbent pairs (refrigerant with high cooling capacities and IL with absorption capacity) competitive to conventional systems as H2 O/LiBr or NH3 /H2 O. Furthermore, the analysis of operating condition effects by COSMO-based/Aspen HYSYS methodology allows selecting refrigerant/IL pairs with maximum efficiency in the cycle for a fixed cooling temperature, revealing additional advantage of the applications of IL in absorption refrigeration technologies.